A Practical Framework for Value Creation in Health Information Systems From an Ecosystem Perspective: Evaluated in the South African Context - Hlongwane, Sanelisiwe; Grobbelaar, Sara S. (Frontiers in Psychology, 2022)
Performance improvement in any field depends on establishing goals that align the interests of relevant stakeholders, which may be defined as creating value for stakeholders. In the healthcare context, the concept of value creation and its analysis from an ecosystem perspective has been neglected and is hard to achieve in practice. This research adopts an innovation ecosystem perspective to develop and evaluate a practical framework to guide value creation for healthcare settings in a developing country context. The resulting framework serves as a tool that can guide stakeholders to co-create value by defining the inputs, activities, and outputs/outcomes to enable the process of value co-creation through a health information system. Design Science Research Methodology (DSRM) was followed to develop the framework (artifact); it entailed the evaluation of the preliminary framework through a range of cycles. A relevance cycle was completed through a literature review. Since the investigation was done from an ecosystem perspective, it provided an understanding of the core characteristics of ecosystems, information systems, and value to inform the development of a preliminary framework. The preliminary framework was evaluated through two design cycles: the first was based on in-depth semi-structured interviews with six industry experts, and the second comprised a framework ranking exercise. The observations from the two stages informed the modification and refinement of framework items. The evaluated framework provides practical and actionable elements of a value creation system based on three canvasses: 1) the pre-use canvas defines the healthcare system and its stakeholders; 2) the tool guideline provides an overview of the development of ecosystem canvas elements, and 3) the ecosystem canvas represents the process of value creation along with a conceptual canvas with descriptions or implications of each of the framework’s concepts.